Matrilineal System Mechanism for The Distribution of Inheritance Rights - Ahmad Jamburi; Mohammad Muhibbin (Jurnal Cakrawala Hukum, 2024)
Inheritance law is one part of civil law and is the smallest part of family law. Inheritance law is closely related to the scope of human life because every human being will experience a legal event called death. In the Unitary State of the Republic of Indonesia territory, various inheritance law systems apply, namely customary inheritance law, Islamic inheritance law, and Western inheritance law, as stated in the Burgerlijk Wetboek (BW). The family system in Indonesian society focuses on the lineage system. In general, there are three kinship systems, namely the patrilineal system (found in communities in Tanah Gayo, Alas, Batak, Ambon, Irian Jaya, Timor, and Bali), the matrilineal system (found in the Minangkabau area), and the bilateral or parental system (found in regions include: Java, Madura, East Sumatra, Riau, Aceh, South Sumatra, all of Kalimantan, all of Sulawesi, Ternate and Lombok). According to Minangkabau customary law, the inheritance distribution system, is based on a descent system drawn from the mother's line, namely a matrilineal inheritance system where the position of children is inherited. Women are the successors, but the heirs are all male and female children from the mother's assets.